A new multilevel DC-AC converter topology with reduced switch using multicarrier sinusoidal pulse width modulation - R. Palanisamy; S. Vidyasagar; V. Kalyanasundaram; D. Karthikeyan; K. Selvakumar; D. Selvabharathi; K. Vijayakumar (Institute of Advanced Engineering and Science, 2020)
Multilevel converters have a significant role in power processing control in the power system, which has some inherent features like reduced harmonics, high power & medium voltage, reduced voltage stress. In this proposed paper, a novel multilevel inverter with reduced number of switches and without passive components. The proposed inverter generates 15 level output voltage with suitable switching pulse generation using multicarrier sinusoidal pulse width modulation (MSPWM) and different level of voltages are obtained with variation of modulation index. Also coupled inductor is used to minimize the harmonic content and smoothing output current. The scheme which includes different range of unequal voltage sources. As a result, the proposed system it reduces switching control complexity and there is no voltage balancing problem. This paper elucidates the operating modes, voltage stress minimisation and harmonic reduction are discussed. The results of the proposed multilevel dc-ac converter are verified using matlab/simulink. The simulation & hardware results of the proposed inverter were verified using matlab simulink and dsPIC controller respectively, which was analysed with different voltage level and different modulation index.